Climate Change And Fisherman Adaptation: Survival Strategy Of Jember Fishermen Based On Local Wisdom - Wirawan, I. B.; Adzkiyah, Adzkiyah (Opción, 2019)
This study is about fishermen’s adaptation strategies in responding to climate change by enabling the potential of local community wisdom in the southern coastal areas of Jember, including Sumberejo Village, Ambulu District, Puger Wetan Village and Puger Kulon Village, Puger District. This type of research is qualitative and uses ethnographic methods. The research approach is de- scriptive analytical. Field findings indicate that various forms of coastal eco- logical changes due to climate change were responded to by fishermen through the local community’s existing wisdom. This research activity is an effort to implement a higher education research strategy plan that focuses on the lead- ing areas of coastal communities and fishermen.